Secondary battery

By using lithium-nickel composite oxide in the positive electrode of secondary batteries and performing XPS analysis, the surface state and structure of the positive electrode are optimized, and the problem of insufficient swelling characteristics in the prior art is solved, and better battery stability and performance are achieved.

JP7648601B2Active Publication Date: 2025-03-18MURATA MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022509244
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2020-11-16
Publication Date
2025-03-18
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

During the performance improvement process of existing secondary batteries, swelling characteristics are still insufficient and further improvement is needed.

Method used

A positive electrode containing lithium nickel composite oxide was used and specific spectra and ratios were detected by surface analysis using X-ray electron energy spectrum (XPS) to optimize the surface state and structure of the positive electrode.

Benefits of technology

By optimizing the surface state and structure of the positive electrode, the swelling characteristics of secondary batteries are significantly improved, ensuring the stability and performance of the battery during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648601000007
    Figure 0007648601000007
  • Figure 0007648601000008
    Figure 0007648601000008
  • Figure 0007648601000009
    Figure 0007648601000009
Patent Text Reader

Abstract

A secondary battery according to the present invention is provided with a positive electrode containing a lithium-nickel composite oxide, a negative electrode, and an electrolytic solution. When surface analysis of the positive electrode is performed by using an X-ray photoelectron spectroscopy analysis method, a first O1s spectrum having a peak within a binding energy range of 528-531 eV inclusive, a second O1s spectrum having a peak within a binding energy range from 531 eV exclusive to 535 eV inclusive, a B1s spectrum, an S2p spectrum, an F1s spectrum, and an Ni3p spectrum are detected. The ratio of the intensity of the first O1s spectrum with respect to the intensity of the second O1s spectrum is 0.5-0.8 inclusive, the ratio of the intensity of the B1s spectrum with respect to the intensity of the Ni3p spectrum is 0.9-1.8 inclusive, the ratio of the intensity of the S2p spectrum with respect to the intensity of the Ni3p spectrum is 0.4-1.2 inclusive, and the ratio of the intensity of the F1s spectrum with respect to the intensity of the Ni3p spectrum is 8-13 inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a secondary battery. [Background technology]

[0002] Due to the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as power sources that are small and lightweight and can obtain high energy density. These secondary batteries include a positive electrode, a negative electrode, and an electrolyte solution, and various studies have been conducted on the configuration of the secondary battery.

[0003] Specifically, various additives are added to the electrolyte to improve various performances (see, for example, Patent Documents 1 to 7). The additives include boric acid compounds (e.g., tetraboric acid), S=O group-containing compounds (e.g., sulfonic acid esters), and lithium salts (e.g., LiPF6). In this case, lithium nickel oxide and lithium nickel composite oxide are used as the positive electrode active material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5645144 specification [Patent Document 2] U.S. Patent No. 7,235,334 [Patent Document 3] JP 2017-157327 A [Patent Document 4] JP 2008-098053 A [Patent Document 5] JP 2010-225522 A [Patent Document 6] JP 2015-090857 A [Patent Document 7] International Publication No. 2016-167316 Brochure Summary of the Invention

[0005] Although various studies have been conducted on improving the performance of secondary batteries, the swelling characteristics are still insufficient, and there is room for further improvement.

[0006] The present technology has been made in view of such problems, and an object of the technology is to provide a secondary battery capable of obtaining excellent swelling characteristics.

[0007] A secondary battery according to an embodiment of the present technology includes a positive electrode containing a lithium nickel composite oxide, a negative electrode, and an electrolyte. In a surface analysis of the positive electrode using X-ray photoelectron spectroscopy, a first O1s spectrum having a peak in a range of binding energy from 528 eV to 531 eV, a second O1s spectrum having a peak in a range of binding energy from 531 eV to 535 eV, a B1s spectrum, an S2p spectrum, an F1s spectrum, and a Ni3p spectrum are detected. The ratio of the intensity of the first O1s spectrum to the intensity of the second O1s spectrum is 0.5 to 0.8, the ratio of the intensity of the B1s spectrum to the intensity of the Ni3p spectrum is 0.9 to 1.8, the ratio of the intensity of the S2p spectrum to the intensity of the Ni3p spectrum is 0.4 to 1.2, and the ratio of the intensity of the F1s spectrum to the intensity of the Ni3p spectrum is 8 to 13.

[0008] The above-mentioned "lithium nickel composite oxide" is a general term for oxides containing lithium and nickel as constituent elements. The lithium nickel composite oxide will be described in detail later.

[0009] According to the secondary battery of the embodiment of the present technology, the positive electrode contains a lithium nickel composite oxide. In addition, the above-mentioned series of XPS spectra are detected in the surface analysis of the positive electrode using X-ray photoelectron spectroscopy, and the series of ratios defined based on the intensities of the series of XPS spectra satisfy the above-mentioned conditions. Therefore, excellent bulge characteristics can be obtained.

[0010] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]

[0011] [Figure 1] 1 is a perspective view illustrating a configuration of a secondary battery according to an embodiment of the present technology. [Diagram 2] 2 is a cross-sectional view illustrating the configuration of the battery element shown in FIG. [Diagram 3] FIG. 1 is a block diagram showing a configuration of an application example of a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Secondary battery 1-1.Configuration 1-2.Physical properties 1-3.Operation 1-4. Manufacturing method 1-5. Actions and Effects 2. Variations 3. Uses of secondary batteries

[0013] <1. Secondary battery> First, a secondary battery according to an embodiment of the present technology will be described.

[0014] The secondary battery described here is a secondary battery that obtains battery capacity by utilizing the absorption and release of an electrode reactant, and includes a positive electrode, a negative electrode, and an electrolyte solution, which is a liquid electrolyte. In this secondary battery, the charge capacity of the negative electrode is larger than the discharge capacity of the positive electrode in order to prevent the electrode reactant from being deposited on the surface of the negative electrode during charging. In other words, the electrochemical capacity per unit area of ​​the negative electrode is set to be larger than the electrochemical capacity per unit area of ​​the positive electrode.

[0015] The type of the electrode reactant is not particularly limited, but specifically, it is a light metal such as an alkali metal or an alkaline earth metal, etc. The alkali metal is lithium, sodium, potassium, etc., and the alkaline earth metal is beryllium, magnesium, calcium, etc.

[0016] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is absorbed and released in an ionic state.

[0017] <1-1. Configuration> Fig. 1 shows a perspective configuration of a secondary battery, and Fig. 2 shows a cross-sectional configuration of the battery element 10 shown in Fig. 1. However, Fig. 1 shows a state in which the battery element 10 and an exterior film 20 are separated from each other, and Fig. 2 shows only a part of the battery element 10.

[0018] 1, this secondary battery includes a battery element 10, an exterior film 20, a positive electrode lead 31, and a negative electrode lead 32. The secondary battery described here is a laminate film type secondary battery that uses a flexible (or pliable) exterior member (exterior film 20) as an exterior member for housing the battery element 10.

[0019] [Exterior film] 1, the exterior film 20 is a single film-like member that can be folded in the direction of the arrow R (dash line). As described above, the exterior film 20 contains the battery element 10, and therefore contains an electrolyte together with the positive electrode 11 and the negative electrode 12 described below. The exterior film 20 is provided with a recessed portion 20U (so-called deep drawing portion) for containing the battery element 10.

[0020] Specifically, the exterior film 20 is a three-layer laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order from the inside, and when the exterior film 20 is folded, the outer peripheral edges of the opposing fusion layers are bonded (fused) to each other. This makes the exterior film 20 bag-shaped so that the battery element 10 can be enclosed therein. The fusion layer contains a polymer compound such as polypropylene. The metal layer contains a metal material such as aluminum. The surface protection layer contains a polymer compound such as nylon.

[0021] However, the configuration (number of layers) of the exterior film 20 is not particularly limited, and may be one or two layers, or may be four or more layers.

[0022] An adhesive film 21 is inserted between the exterior film 20 and the positive electrode lead 31, and an adhesive film 22 is inserted between the exterior film 20 and the negative electrode lead 32. Each of the adhesive films 21, 22 is a member that prevents outside air from entering the interior of the exterior film 20, and contains one or more types of polymer compounds such as polyolefins that have adhesive properties to each of the positive electrode lead 31 and the negative electrode lead 32. The polyolefins are polyethylene, polypropylene, modified polyethylene, modified polypropylene, and the like. However, one or both of the adhesive films 21, 22 may be omitted.

[0023] [Battery element] 1 and 2, the battery element 10 is housed inside an exterior film 20, and includes a positive electrode 11, a negative electrode 12, a separator 13, and an electrolyte (not shown). The electrolyte is impregnated into each of the positive electrode 11, the negative electrode 12, and the separator 13.

[0024] This battery element 10 is a structure (wound electrode body) in which a positive electrode 11 and a negative electrode 12 are stacked on top of each other with a separator 13 interposed therebetween, and the positive electrode 11, the negative electrode 12, and the separator 13 are wound around a winding axis. Therefore, the positive electrode 11 and the negative electrode 12 face each other with the separator 13 interposed therebetween. The winding axis is a virtual axis extending in the Y-axis direction.

[0025] Here, the three-dimensional shape of the battery element 10 is a flat shape. That is, the shape of the cross section (cross section along the XZ plane) of the battery element 10 intersecting with the winding axis is a flat shape defined by a major axis and a minor axis, more specifically, a flattened, approximately elliptical shape. The major axis is an imaginary axis that extends in the X-axis direction and has a relatively large length, and the minor axis is an imaginary axis that extends in the Z-axis direction intersecting with the X-axis direction and has a relatively small length.

[0026] (positive electrode) 2, the positive electrode 11 includes a positive electrode collector 11A having a pair of surfaces, and two positive electrode active material layers 11B and two coatings 11C disposed on both surfaces of the positive electrode collector 11A, and the coatings 11C cover the surface of the positive electrode active material layer 11B. However, the positive electrode active material layer 11B may be disposed on only one surface of the positive electrode collector 11A on the side where the positive electrode 11 faces the negative electrode 12.

[0027] The positive electrode current collector 11A contains one or more kinds of conductive materials such as metal materials, and the metal materials are aluminum, nickel, stainless steel, etc. The positive electrode active material layer 11B contains one or more kinds of positive electrode active materials capable of absorbing and releasing lithium, and may further contain a positive electrode binder, a positive electrode conductive agent, etc.

[0028] The positive electrode active material contains a lithium-containing compound, and more specifically, contains one or more of lithium nickel composite oxides. As described above, the "lithium nickel composite oxide" is a general term for oxides containing lithium and nickel as constituent elements, and has a layered rock salt crystal structure. The positive electrode active material contains the lithium nickel composite oxide because it can obtain a high energy density.

[0029] The type (composition) of the lithium nickel composite oxide is not particularly limited as long as it is an oxide containing lithium and nickel as constituent elements. Among them, it is preferable that the lithium nickel composite oxide contains a compound represented by the following formula (1). This is because a sufficiently high energy density can be obtained.

[0030] Li w Ni (1-x-y-z) Co x M1 y M2 z O2···(1) (M1 is at least one of Al and Mn. M2 is at least one of elements belonging to groups 2 to 15 of the long-form periodic table (excluding Ni, Co, Al, and Mn). w, x, y, and z satisfy 0.8≦w≦1.2, 0≦x≦0.3, 0≦y≦0.1, and 0≦z≦0.1. However, the composition of lithium varies depending on the charge / discharge state, and w is the value in a fully discharged state.)

[0031] The compound shown in formula (1) (lithium nickel composite oxide) is an oxide that contains lithium and nickel as well as cobalt and other elements (M1 and M2) as necessary as constituent elements.

[0032] In detail, as is clear from the range of values ​​that w can take (0.8≦w≦1.2), the lithium nickel composite oxide contains lithium as a constituent element.

[0033] As is clear from the range of values ​​that x can take (0≦x≦0.3), the lithium nickel composite oxide may or may not contain cobalt as a constituent element.

[0034] As is clear from the range of values ​​that y can take (0≦y≦0.1), the lithium nickel composite oxide may or may not contain another element (M1) as a constituent element.

[0035] In particular, when the lithium nickel composite oxide contains another element (M1) as a constituent element, the lithium nickel composite oxide may contain only aluminum as a constituent element, may contain only manganese as a constituent element, or may contain both aluminum and manganese as constituent elements.

[0036] As is clear from the range of values ​​that z can take (0≦z≦0.1), the lithium nickel composite oxide may or may not contain another element (M2) as a constituent element.

[0037] In particular, when the lithium nickel composite oxide contains another element (M2) as a constituent element, the type of the other element (M2) may be only one type, or may be two or more types.

[0038] As is clear from the range of values ​​that x, y, and z can each take, (1-xyz)≧0.5, and therefore the lithium nickel composite oxide contains nickel as a constituent element.

[0039] Specific examples of lithium nickel composite oxides are LiNiO2, LiNi 0.70 Co 0.30 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.50 Co 0.20 Mn 0.30 O2 and LiNi 0.80 Co0.10 Al 0.05 Mn 0.05 O2, etc.

[0040] As long as the positive electrode active material contains the above-mentioned lithium nickel composite oxide, it may further contain one or more of other lithium-containing compounds.

[0041] The type of the other lithium-containing compound is not particularly limited, but specifically includes lithium transition metal compounds. The "lithium transition metal compound" is a general term for compounds containing lithium and one or more transition metal elements as constituent elements, and may further contain one or more other elements. The type of the other element is not particularly limited as long as it is an element other than a transition metal element, but specifically, it is an element belonging to Groups 2 to 15 of the long periodic table. However, the lithium nickel composite oxide described above is excluded from the lithium transition metal compound described here.

[0042] The type of lithium transition metal compound is not particularly limited, but specific examples include oxides, phosphate compounds, silicate compounds, and borate compounds. Specific examples of oxides include LiCoO2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.2 Mn 0.52 Co 0.175 Ni 0.1 O2, Li 1.15 (M 0.65 Ni 0.22 Co 0.13 )O2 and LiMn2O4. Specific examples of phosphate compounds include LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 PO4 and LiFe 0.3 Mn 0.7 PO4, etc.

[0043] The positive electrode binder contains one or more of synthetic rubbers and polymeric compounds. Synthetic rubbers include styrene-butadiene rubbers, fluorine-based rubbers, and ethylene-propylene-diene rubbers. Polymeric compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.

[0044] The positive electrode conductive agent contains one or more conductive materials such as carbon materials, and the carbon materials are graphite, carbon black, acetylene black, ketjen black, etc. However, the conductive material may also be a metal material, a polymer compound, etc.

[0045] The method for forming the positive electrode active material layer 11B is not particularly limited, but specifically, it is any one or more of coating methods.

[0046] The coating 11C is a film formed on the surface of the positive electrode active material layer 11B by utilizing the charging and discharging of the secondary battery, and more specifically, is a deposition film deposited on the surface of the positive electrode active material layer 11B due to the decomposition reaction of the electrolyte during charging and discharging.

[0047] This coating 11C is formed on the surface of the positive electrode active material layer 11B mainly in response to charging and discharging during a stabilization treatment of the secondary battery described below, i.e., the first charging and discharging after the secondary battery is assembled. However, the coating 11C may be additionally formed on the surface of the positive electrode active material layer 11B in response to charging and discharging after the stabilization treatment of the secondary battery, i.e., charging and discharging after the secondary battery is completed.

[0048] The coating 11C may cover the entire surface of the positive electrode active material layer 11B, or may cover only a portion of the surface of the positive electrode active material layer 11B. Of course, in the latter case, a plurality of coatings 11C may cover the surface of the positive electrode active material layer 11B at a plurality of locations spaced apart from one another.

[0049] Here, the coating 11C is provided so as to cover the surface of each of the two positive electrode active material layers 11B, so that the positive electrode 11 includes two coatings 11C. However, since the coating 11C is provided so as to cover the surface of only one of the two positive electrode active material layers 11B, the positive electrode 11 may include one coating 11C.

[0050] In particular, in the coating 11C, as described below, in a surface analysis of the positive electrode 11 (coating 11C) using X-ray Photoelectron Spectroscopy (XPS), predetermined XPS spectra (B1s spectrum, S2p spectrum, and F1s spectrum) are obtained. Therefore, the coating 11C contains boron, sulfur, and fluorine as constituent elements.

[0051] More specifically, as described below, when the electrolyte contains a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound, the coating 11C is formed due to the decomposition reaction of the electrolyte, and therefore, as described above, the coating 11C contains boron, sulfur, and fluorine as constituent elements.

[0052] In this coating 11C, the physical properties defined by the analysis results of the positive electrode 11 (coating 11C) using XPS are optimized in order to suppress the decomposition reaction of the electrolyte on the surface of the positive electrode 11 and thereby suppress the generation of gas due to the decomposition reaction of the electrolyte. The physical properties of the positive electrode 11 (coating 11C) described here will be described in detail later.

[0053] (Negative electrode) 2, the negative electrode 12 includes a negative electrode current collector 12A having a pair of surfaces, and two negative electrode active material layers 12B disposed on both surfaces of the negative electrode current collector 12A. However, the negative electrode active material layer 12B may be disposed on only one surface of the negative electrode current collector 12A on the side where the negative electrode 12 faces the positive electrode 11.

[0054] The negative electrode current collector 12A contains any one or two or more kinds of conductive materials such as metal materials, and the metal materials include copper, aluminum, nickel, stainless steel, etc. The negative electrode active material layer 12B contains any one or two or more kinds of negative electrode active materials capable of occluding and releasing lithium, and may further contain a negative electrode binder, a negative electrode conductive agent, etc. Details regarding the negative electrode binder are the same as those regarding the positive electrode binder, and details regarding the negative electrode conductive agent are the same as those regarding the positive electrode conductive agent.

[0055] The type of the negative electrode active material is not particularly limited, but specifically, it is a carbon material, a metal-based material, etc. The carbon material includes graphitizable carbon, non-graphitizable carbon, graphite, etc., and the graphite includes natural graphite, artificial graphite, etc. The metal-based material is a material containing any one or two or more kinds of metal elements and metalloid elements capable of forming an alloy with lithium. The types of the metal elements and metalloid elements are not particularly limited, but specifically, they are silicon, tin, etc. However, the metal-based material may be a single substance, an alloy, a compound, a mixture of two or more of them, or a material containing two or more phases of them.

[0056] Specific examples of the metal-based material are SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, SiC, Si3N4, Si2N2O, SiO v (0 < v ≤ 2), LiSiO, SnO w (0 < w ≤ 2), SnSiO3, LiSnO, and Mg2Sn, etc. However, for SiO v the v may satisfy 0.2 < v < 1.4.

[0057] The method for forming the negative electrode active material layer 12B is not particularly limited, but specifically, it is any one or two or more of a coating method, a vapor phase method, a liquid phase method, a spraying method, a firing method (sintering method), etc.

[0058] (Separator) 2, the separator 13 is an insulating porous film interposed between the positive electrode 11 and the negative electrode 12, and allows lithium ions to pass through while preventing contact between the positive electrode 11 and the negative electrode 12. The separator 13 contains one or more types of polymer compounds such as polytetrafluoroethylene, polypropylene, and polyethylene.

[0059] (electrolyte) The electrolyte includes a solvent and an electrolyte salt.

[0060] The solvent contains one or more of non-aqueous solvents (organic solvents), and the electrolyte containing the non-aqueous solvent is a so-called non-aqueous electrolyte. The non-aqueous solvent is an ester or ether, more specifically, a carbonate ester compound, a carboxylate ester compound, a lactone compound, etc. This is because the dissociation of the electrolyte salt is improved and high ion mobility is obtained.

[0061] Specifically, the carbonate ester-based compound is a cyclic carbonate ester, a chain carbonate ester, etc. Specific examples of the cyclic carbonate ester are ethylene carbonate and propylene carbonate, and specific examples of the chain carbonate ester are dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc.

[0062] The carboxylate-based compound is a carboxylate, etc. Specific examples of the carboxylate are ethyl acetate, ethyl propionate, propyl propionate, and ethyl trimethylacetate.

[0063] The lactone compound is lactone, etc. Specific examples of lactone are γ-butyrolactone and γ-valerolactone, etc. In addition to the above-mentioned lactone compounds, the ethers may be 1,2-dimethoxyethane, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, etc.

[0064] The non-aqueous solvent may also be an unsaturated cyclic carbonate, a halogenated carbonate, a sulfonate, a phosphate, an acid anhydride, a nitrile compound, an isocyanate compound, or the like, because the chemical stability of the electrolyte solution is improved.

[0065] Specifically, the unsaturated cyclic carbonates include vinylene carbonate (1,3-dioxol-2-one), vinyl ethylene carbonate (4-vinyl-1,3-dioxolan-2-one) and methylene ethylene carbonate (4-methylene-1,3-dioxolan-2-one). The halogenated carbonates include fluoroethylene carbonate (4-fluoro-1,3-dioxolan-2-one) and difluoroethylene carbonate (4,5-difluoro-1,3-dioxolan-2-one). The sulfonic acid esters include 1,3-propane sultone and 1,3-propene sultone. The phosphate esters include trimethyl phosphate and triethyl phosphate.

[0066] The acid anhydrides include cyclic dicarboxylic acid anhydrides, cyclic disulfonic acid anhydrides, and cyclic carboxylic acid sulfonic acid anhydrides. The cyclic dicarboxylic acid anhydrides include succinic acid anhydride, glutaric acid anhydride, and maleic acid anhydride. The cyclic disulfonic acid anhydrides include 1,2-ethane disulfonic acid anhydride and 1,3-propane disulfonic acid anhydride. The cyclic carboxylic acid sulfonic acid anhydrides include sulfobenzoic acid anhydride, sulfopropionic acid anhydride, and sulfobutyric acid anhydride.

[0067] The nitrile compounds include acetonitrile, succinonitrile, and adiponitrile. The isocyanate compounds include hexamethylene diisocyanate.

[0068] The electrolyte salt includes any one or more of light metal salts such as lithium salts, such as lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium tris(trifluoromethanesulfonyl)methide (LiC(CF3SO2)3), lithium difluorooxalatoborate (LiBF2(C2O4)), and lithium bis(oxalato)borate (LiB(C2O4)2).

[0069] The content of the electrolyte salt is not particularly limited, but specifically, it is 0.3 mol / kg to 3.0 mol / kg relative to the solvent, because high ionic conductivity can be obtained.

[0070] In addition, in order to obtain the above-mentioned physical properties based on the results of the surface analysis of the positive electrode 11 (coating 11C) using XPS, the electrolyte may contain a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound. The details of the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound described here will be described later.

[0071] [Positive and negative leads] The positive electrode lead 31 is a positive electrode terminal connected to the positive electrode 11 (positive electrode current collector 11A) and contains one or more types of conductive materials such as aluminum. The negative electrode lead 32 is a negative electrode terminal connected to the negative electrode 12 (negative electrode current collector 12A) and contains one or more types of conductive materials such as copper, nickel, and stainless steel. The shapes of the positive electrode lead 31 and the negative electrode lead 32 are not particularly limited, but are specifically one or more types of a thin plate shape, a mesh shape, and the like.

[0072] 1, the positive electrode lead 31 and the negative electrode lead 32 are each led out in a common direction from the inside to the outside of the exterior film 20. However, the positive electrode lead 31 and the negative electrode lead 32 may each be led out in directions different from each other.

[0073] Here, the number of the positive electrode leads 31 is one. However, the number of the positive electrode leads 31 is not particularly limited and may be two or more. In particular, when the number of the positive electrode leads 31 is two or more, the electrical resistance of the secondary battery decreases. The explanation regarding the number of the positive electrode leads 31 here is also applicable to the number of the negative electrode leads 32, so the number of the negative electrode leads 32 is not limited to one and may be two or more.

[0074] <1-2.Physical properties> As described above, in this secondary battery, the physical properties defined by the results of the surface analysis of the positive electrode 11 (coating 11C) using XPS are optimized.

[0075] Specifically, in a surface analysis of the positive electrode 11 (coating 11C) using XPS, the following six types of XPS spectra are detected.

[0076] The first XPS spectrum is an O1s spectrum caused by oxygen, more specifically, a first O1s spectrum having a peak in a binding energy range of 528 eV to 531 eV. This first O1s spectrum is considered to be detected mainly due to the components of the positive electrode active material layer 11B (lithium nickel composite oxide as the positive electrode active material), the bonding state of oxygen atoms in the crystal structure of the positive electrode active material, and the components of the coating 11C.

[0077] The second XPS spectrum is another O1s spectrum caused by oxygen, more specifically, a second O1s spectrum having a peak in a range of binding energies greater than 531 eV and equal to or less than 535 eV. This second O1s spectrum, like the first O1s spectrum described above, is considered to be detected mainly due to the components of the positive electrode active material layer 11B (positive electrode active material), the bonding state of oxygen atoms in the crystal structure of the positive electrode active material, and the components of the coating 11C.

[0078] The third XPS spectrum is a B1s spectrum caused by boron, which is believed to be detected mainly due to the components of the coating 11C.

[0079] The fourth XPS spectrum is an S2p spectrum caused by sulfur. This S1s spectrum is considered to be detected mainly due to the constituents of the coating 11C.

[0080] The fifth XPS spectrum is an F1s spectrum caused by fluorine. This F1s spectrum is detected mainly due to the components of the coating 11C, and the components of the coating 11C are considered to be LiF and the like.

[0081] The sixth XPS spectrum is a Ni3p spectrum caused by nickel. This Ni3p spectrum is considered to be detected mainly due to the components of the positive electrode active material layer 11B (positive electrode active material) and the bonding state of nickel atoms in the crystal structure of the positive electrode active material.

[0082] In this case, the four ratios (intensity ratios) defined based on the intensities of the six types of XPS spectra described above satisfy the following conditions.

[0083] First, the intensity ratio IO (=IO1 / IO2), which is the ratio of the intensity IO1 of the first O1s spectrum to the intensity IO2 of the second O1s spectrum, is 0.5 to 0.8.

[0084] Secondly, the intensity ratio IBN (=IB / IN), which is the ratio of the intensity IB of the B1s spectrum to the intensity IN of the Ni3p spectrum, is 0.9 to 1.8.

[0085] Third, the intensity ratio ISN (=IS / IN), which is the ratio of the intensity IS of the S2p spectrum to the intensity IN of the Ni3p spectrum, is 0.4 to 1.2.

[0086] Fourth, the intensity ratio IFN (=IF / IN), which is the ratio of the intensity IF of the F1s spectrum to the intensity IN of the Ni3p spectrum, is 8-13.

[0087] The intensity ratios IO, IBN, ISN, and IFN satisfy the above conditions because the bonding state (oxidation state) of constituent atoms such as oxygen atoms and nickel atoms in the crystal structure of the positive electrode active material (lithium nickel composite oxide) in the positive electrode 11 is optimized, stabilizing the crystal structure of the positive electrode active material and electrochemically stabilizing the surface state of the positive electrode 11 by utilizing the coating 11C. This suppresses the decomposition reaction of the electrolyte on the surface of the positive electrode 11 during charging and discharging, thereby suppressing the generation of gas due to the decomposition reaction of the electrolyte. Therefore, even if the positive electrode 11 contains a lithium nickel composite oxide, swelling of the secondary battery during charging and discharging is suppressed.

[0088] Here, in order to enable the above-mentioned B1s spectrum, S2p spectrum, and F1s spectrum to be detected in the surface analysis of the positive electrode 11 using XPS, the electrolyte may contain a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound.

[0089] The boron-containing compound is a general term for compounds that contain boron as a constituent element. The type of the boron-containing compound is not particularly limited, but specifically, it is one or more types of boron-containing lithium salts.

[0090] Specific examples of boron-containing lithium salts include lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium bis(oxalato)borate, which have already been described as candidates for the electrolyte salt.

[0091] Sulfur-containing compound is a general term for compounds that contain sulfur as a constituent element. The type of sulfur-containing compound is not particularly limited, but specifically, it is one or more of cyclic disulfonic acid anhydrides and alkynyl sulfonates. That is, the sulfur-containing compound may be only cyclic disulfonic acid anhydrides, only alkynyl sulfonates, or both cyclic disulfonic acid anhydrides and alkynyl sulfonates.

[0092] A cyclic disulfonic acid anhydride is a cyclic compound obtained by dehydrating a disulfonic acid anhydride. Specific examples of cyclic disulfonic acid anhydrides include 1,2-ethane disulfonic acid anhydride and 1,3-propane disulfonic acid anhydride, which have already been described as candidates for the non-aqueous solvent. In addition, the cyclic disulfonic acid anhydride may be 1,2-benzene disulfonic acid anhydride.

[0093] Alkynyl sulfonates are sulfonic acids containing a carbon-carbon triple bond. Specific examples of alkynyl sulfonates include propargyl benzenesulfonate and propargyl methanesulfonate.

[0094] The fluorine-containing compound is a general term for compounds that contain fluorine as a constituent element. The type of the fluorine-containing compound is not particularly limited, but specifically, it is one or more of fluorine-containing lithium salts.

[0095] Specific examples of the fluorine-containing lithium salt include lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tris(trifluoromethanesulfonyl)methide, which have already been described as candidates for the electrolyte salt. In addition, the fluorine-containing lithium salt may be lithium hexafluoroarsenate (LiAsF6), etc.

[0096] However, a compound containing both boron and fluorine as constituent elements is considered to be a boron-containing compound, not a fluorine-containing compound. Therefore, as described above, a lithium salt containing both boron and fluorine as constituent elements (lithium tetrafluoroborate) is considered to be a boron-containing compound (boron-containing lithium salt), not a fluorine-containing compound (fluorine-containing lithium salt).

[0097] The content of the boron-containing compound in the electrolyte is not particularly limited and can be set arbitrarily. The same applies to the content of the sulfur-containing compound in the electrolyte and the content of the fluorine-containing compound in the electrolyte.

[0098] In addition, to confirm, as long as six kinds of XPS spectra are detected in the surface analysis of the positive electrode 11 using XPS and the intensity ratio of four kinds satisfies the above-mentioned conditions, the electrolyte does not necessarily have to contain a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound. In this case, the electrolyte does not necessarily have to contain all of the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound, and may contain only any one or two of the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound.

[0099] Specifically, even if the electrolyte initially contains all of the boron-containing compound, sulfur-containing compound, and fluorine-containing compound, when all of the boron-containing compound, sulfur-containing compound, and fluorine-containing compound are consumed to form the coating 11C during charging and discharging during the stabilization treatment of the secondary battery, the electrolyte in the completed secondary battery may not contain the boron-containing compound, sulfur-containing compound, or fluorine-containing compound.

[0100] In addition, even if the electrolyte initially contains all of the boron-containing compound, sulfur-containing compound, and fluorine-containing compound, if any one or two of the boron-containing compound, sulfur-containing compound, and fluorine-containing compound are consumed to form the coating 11C during charging and discharging during the stabilization treatment of the secondary battery, the electrolyte in the completed secondary battery may contain only the remaining one or two of the boron-containing compound, sulfur-containing compound, and fluorine-containing compound.

[0101] <1-3. Operation> When the secondary battery is charged, lithium is released from the positive electrode 11 and is absorbed in the negative electrode 12 via the electrolyte. When the secondary battery is discharged, lithium is released from the negative electrode 12 and is absorbed in the positive electrode 11 via the electrolyte. During these charge and discharge operations, lithium is absorbed and released in an ionic state.

[0102] <1-4. Manufacturing method> When manufacturing a secondary battery, the positive electrode 11 and the negative electrode 12 are produced and an electrolyte solution is prepared according to the procedure described below, and then the positive electrode 11, the negative electrode 12, and the electrolyte solution are used to manufacture a secondary battery.

[0103] [Preparation of positive electrode] Here, a case will be taken as an example in which the lithium nickel composite oxide, which is the positive electrode active material, contains cobalt and other elements (M1, M2) as constituent elements.

[0104] First, as raw materials, a lithium supply source (lithium compound), a nickel supply source (nickel compound), a cobalt supply source (cobalt compound), a supply source of other element (M1) (first other element compound), and a supply source of other element (M2) (second other element compound) are prepared.

[0105] The lithium compound may be an inorganic compound or an organic compound, and the type of the lithium compound may be one or more. Specific examples of the lithium compound that is an inorganic compound include lithium hydroxide, lithium carbonate, lithium nitrate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium chlorate, lithium perchlorate, lithium bromate, lithium iodate, lithium oxide, lithium peroxide, lithium sulfide, lithium hydrogen sulfide, lithium sulfate, lithium hydrogen sulfate, lithium nitride, lithium azide, lithium nitrite, lithium phosphate, lithium dihydrogen phosphate, and lithium hydrogen carbonate. Specific examples of the lithium compound that is an organic compound include methyl lithium, vinyl lithium, isopropyl lithium, butyl lithium, phenyl lithium, lithium oxalate, and lithium acetate.

[0106] The description of the lithium compound here is the same for the nickel compound, the cobalt compound, the first other element compound, and the second other element compound. That is, the nickel compound may be either an inorganic compound or an organic compound, and the type of the nickel compound may be one or more than one. In addition, the specific example of the nickel compound is a compound in which the lithium in the specific example of the lithium compound is replaced with nickel.

[0107] Then, the lithium compound, the nickel compound, the cobalt compound, the first compound of other element, and the second compound of other element are mixed to obtain a precursor. The mixing ratio of the lithium compound, the nickel compound, the cobalt compound, the first compound of other element, and the second compound of other element is determined according to the composition of the lithium nickel composite oxide to be finally obtained.

[0108] Next, the precursor is calcined. The calcination temperature and other conditions can be set as desired. This synthesizes a compound (lithium nickel composite oxide) containing lithium, nickel, cobalt, and other elements (M1, M2) as constituent elements, thereby obtaining a positive electrode active material (lithium nickel composite oxide).

[0109] In this case, the intensity ratio IO can be adjusted by changing the conditions such as the sintering temperature, since the intensity IO1 of the first O1s spectrum and the intensity IO2 of the second O1s spectrum change. Also, the intensity IN of the Ni3p spectrum changes by changing the conditions such as the sintering temperature and sintering time.

[0110] When synthesizing the positive electrode active material (lithium nickel composite oxide), the intensity IN of the Ni3p spectrum changes by changing the composition (nickel content) of the lithium nickel composite oxide, and therefore each of the intensity ratios IBN, ISN, and IFN can be adjusted.

[0111] Next, the above-mentioned positive electrode active material (lithium nickel composite oxide) is mixed with a positive electrode binder and a positive electrode conductive agent to prepare a positive electrode mixture. Next, the positive electrode mixture is poured into an organic solvent or the like to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of the positive electrode collector 11A to form a positive electrode active material layer 11B. After this, the positive electrode active material layer 11B may be compression molded using a roll press or the like. In this case, the positive electrode active material layer 11B may be heated, or compression molding may be repeated multiple times. Finally, a coating 11C is formed on the surface of the positive electrode active material layer 11B by performing a stabilization process for the secondary battery described later. As a result, the positive electrode active material layer 11B and the coating 11C are formed on both sides of the positive electrode collector 11A, and thus the positive electrode 11 is produced.

[0112] [Preparation of negative electrode] The negative electrode active material layer 12B is formed on both sides of the negative electrode current collector 12A by a procedure almost similar to that of the above-mentioned positive electrode 11. Specifically, the negative electrode active material is mixed with a negative electrode binder, a negative electrode conductive agent, and the like to prepare a negative electrode mixture, and then the negative electrode mixture is poured into an organic solvent or the like to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 12A to form the negative electrode active material layer 12B. After this, the negative electrode active material layer 12B may be compression molded. As a result, the negative electrode active material layer 12B is formed on both sides of the negative electrode current collector 12A, and the negative electrode 12 is produced.

[0113] [Preparation of electrolyte] After the electrolyte salt and the like are added to the solvent, the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound are added to the solvent, whereby the electrolyte salt, the boron-containing compound, the sulfur-containing compound, the fluorine-containing compound, and the like are dispersed or dissolved in the solvent, and thus an electrolytic solution is prepared.

[0114] When a boron-containing lithium salt is used as the boron-containing compound, the boron-containing lithium salt may also serve as the electrolyte salt. Similarly, when a fluorine-containing lithium salt is used as the fluorine-containing compound, the fluorine-containing lithium salt may also serve as the electrolyte salt.

[0115] In this case, by changing the content of the boron-containing compound, the intensity IB of the B1s spectrum changes, and the intensity ratio IBN can be adjusted. In addition, by changing the content of the sulfur-containing compound, the intensity IS of the S2p spectrum changes, and the intensity ratio ISN can be adjusted. Furthermore, by changing the content of the fluorine-containing compound, the intensity IF of the F1s spectrum changes, and the intensity ratio IFN can be adjusted.

[0116] As described above, when synthesizing the positive electrode active material, the intensity IN changes according to changes in the sintering temperature, etc. Therefore, each of the intensity ratios IBN, ISN, and IFN can be adjusted by changing the intensity IN.

[0117] [Secondary battery assembly] First, the positive electrode lead 31 is connected to the positive electrode 11 (positive electrode current collector 11A) by welding or the like, and the negative electrode lead 32 is connected to the negative electrode 12 (negative electrode current collector 12A) by welding or the like.

[0118] Next, the positive electrode 11 and the negative electrode 12 are stacked on top of each other with the separator 13 interposed therebetween, and then the positive electrode 11, the negative electrode 12, and the separator 13 are wound to produce a wound body. This wound body has a configuration similar to that of the battery element 10, except that the positive electrode 11, the negative electrode 12, and the separator 13 are not impregnated with an electrolyte. Next, the wound body is pressed using a press or the like to form the wound body into a flat shape.

[0119] Next, after the roll is accommodated inside the recessed portion 20U, the exterior film 20 (adhesive layer / metal layer / surface protection layer) is folded to face the exterior films 20. Next, the outer peripheral edges of two sides of the opposing exterior films 20 (adhesive layers) are bonded to each other using a heat fusion method or the like, thereby accommodating the roll inside the bag-shaped exterior film 20.

[0120] Finally, after injecting an electrolyte solution into the bag-shaped exterior film 20, the outer peripheral edges of the remaining side of the exterior film 20 (adhesive layer) are bonded to each other using a heat fusion method or the like. In this case, an adhesive film 21 is inserted between the exterior film 20 and the positive electrode lead 31, and an adhesive film 22 is inserted between the exterior film 20 and the negative electrode lead 32. As a result, the wound body is impregnated with the electrolyte solution, and the battery element 10, which is a wound electrode body, is produced. Thus, the battery element 10 is enclosed inside the bag-shaped exterior film 20, and a secondary battery is assembled.

[0121] [Stabilization process] The secondary battery is stabilized by charging and discharging the assembled secondary battery. Various conditions such as the environmental temperature, the number of charging and discharging (number of cycles), and the charging and discharging conditions can be set arbitrarily. As a result, as described above, the coating 11C is formed on the surface of the positive electrode active material layer 11B, and the positive electrode 11 is produced. In this case, a coating is also formed on the surface of the negative electrode 12. As a result, the state of the secondary battery is electrochemically stabilized, and a secondary battery using the exterior film 20, i.e., a laminate film type secondary battery, is completed.

[0122] <1-5. Actions and Effects> In this secondary battery, the positive electrode 11 contains a positive electrode active material (lithium nickel composite oxide). In addition, in a surface analysis of the positive electrode 11 using XPS, six types of XPS spectra (first O1s spectrum, second O1s spectrum, B1s spectrum, S2p spectrum, F1s spectrum, and Ni3p spectrum) are detected, and four types of intensity ratios (intensity ratios IO, IBN, ISN, and IFN) satisfy the above-mentioned conditions.

[0123] In this case, as described above, in the positive electrode 11 containing the positive electrode active material (lithium nickel composite oxide), the bonding state (oxidation state) of constituent atoms such as oxygen atoms and nickel atoms in the crystal structure of the positive electrode active material is optimized, so that the crystal structure of the positive electrode active material is stabilized and the surface state of the positive electrode 11 is electrochemically stabilized. As a result, the decomposition reaction of the electrolyte on the surface of the positive electrode 11 during charging and discharging is suppressed, so that the generation of gas due to the decomposition reaction of the electrolyte is suppressed. Therefore, even if the positive electrode 11 contains the lithium nickel composite oxide, the swelling of the secondary battery during charging and discharging is suppressed, so that excellent swelling characteristics can be obtained.

[0124] In particular, if the positive electrode 11 includes a positive electrode active material layer 11B (containing a lithium nickel composite oxide) and a coating 11C (containing boron, sulfur, and fluorine as constituent elements) and the coating 11C is analyzed in a surface analysis of the positive electrode 11 using XPS, the surface state of the positive electrode 11 can be easily stabilized electrochemically by utilizing the coating 11C, thereby achieving a greater effect.

[0125] Furthermore, if the lithium nickel composite oxide contains the compound represented by formula (1), a sufficiently high energy density can be obtained, and therefore a higher effect can be obtained.

[0126] Furthermore, if the electrolyte contains a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound, the six types of XPS spectra are easier to detect, and the intensity ratios of the four types are more likely to satisfy the above-mentioned conditions, thereby achieving even greater effects.

[0127] In this case, if the boron-containing compound contains a boron-containing lithium salt, the sulfur-containing compound contains one or both of a cyclic disulfonic acid anhydride and an alkynyl sulfonate, and the fluorine-containing compound contains a fluorine-containing lithium salt, the six types of XPS spectra can be easily detected stably, and the intensity ratios of the four types can more easily satisfy the above-mentioned conditions, thereby achieving even greater effects.

[0128] Furthermore, if the secondary battery is provided with an exterior film 20 and the battery element 10 (positive electrode 11, negative electrode 12, and electrolyte) is housed inside the exterior film 20, the secondary battery is effectively prevented from swelling even when an exterior film 20 that is prone to swelling is used, thereby achieving a greater effect.

[0129] Furthermore, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing the absorption and release of lithium, so that a higher effect can be obtained.

[0130] <2. Modifications> Next, modified examples of the secondary battery described above will be described. The configuration of the secondary battery can be modified as appropriate, as described below. However, any two or more of the modified examples described below may be combined with each other.

[0131] [Variation 1] A porous membrane separator 13 was used. However, although not specifically shown here, a laminated separator including a polymer compound layer may be used instead of the porous membrane separator 13.

[0132] Specifically, the laminated separator includes a porous membrane having a pair of surfaces and a polymer compound layer disposed on one or both surfaces of the porous membrane. This is because the adhesiveness of the separator to each of the positive electrode 11 and the negative electrode 12 is improved, so that the battery element 10 is less likely to be displaced. This makes it difficult for the secondary battery to swell even if a decomposition reaction of the electrolyte occurs. The polymer compound layer includes a polymer compound such as polyvinylidene fluoride. This is because polyvinylidene fluoride and the like have excellent physical strength and are electrochemically stable.

[0133] One or both of the porous film and the polymer compound layer may contain one or more of a plurality of insulating particles. This is because the plurality of insulating particles dissipate heat when the secondary battery generates heat, improving the safety (heat resistance) of the secondary battery. The insulating particles are inorganic particles and resin particles. Specific examples of inorganic particles are particles of aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide, zirconium oxide, and the like. Specific examples of resin particles are particles of acrylic resin and styrene resin, and the like.

[0134] When preparing a laminated separator, a precursor solution containing a polymer compound and an organic solvent is prepared, and then the precursor solution is applied to one or both sides of a porous film. Alternatively, the porous film may be immersed in the precursor solution. In this case, a plurality of insulating particles may be added to the precursor solution as necessary.

[0135] Even when this laminated separator is used, lithium ions are able to move between positive electrode 11 and negative electrode 12, and therefore the same effect can be obtained.

[0136] [Variation 2] An electrolyte solution, which is a liquid electrolyte, was used, but an electrolyte layer, which is a gel electrolyte, may be used instead of the electrolyte solution, although this is not specifically shown.

[0137] In a battery element 10 using an electrolyte layer, a positive electrode 11 and a negative electrode 12 are laminated with a separator 13 and an electrolyte layer interposed therebetween, and then the positive electrode 11, the negative electrode 12, the separator 13, and the electrolyte layer are wound. The electrolyte layer is interposed between the positive electrode 11 and the separator 13, and is also interposed between the negative electrode 12 and the separator 13.

[0138] Specifically, the electrolyte layer contains a polymer compound together with an electrolytic solution, and in the electrolyte layer, the electrolytic solution is held by the polymer compound. This is because leakage of the electrolytic solution is prevented. The composition of the electrolytic solution is as described above. The polymer compound contains polyvinylidene fluoride and the like. When forming the electrolyte layer, a precursor solution containing an electrolytic solution, a polymer compound, an organic solvent, and the like is prepared, and then the precursor solution is applied to one or both sides of each of the positive electrode 11 and the negative electrode 12.

[0139] Even when this electrolyte layer is used, lithium ions can move between positive electrode 11 and negative electrode 12 via the electrolyte layer, so that the same effect can be obtained.

[0140] <3. Uses of secondary batteries> Next, uses (application examples) of the above-mentioned secondary battery will be described.

[0141] The use of the secondary battery is not particularly limited as long as it is mainly used for machines, devices, instruments, equipment, and systems (assembly of multiple devices, etc.) in which the secondary battery can be used as a driving power source or a power storage source for power accumulation. The secondary battery used as a power source may be a main power source or an auxiliary power source. A main power source is a power source that is used preferentially regardless of the presence or absence of other power sources. An auxiliary power source may be a power source used in place of the main power source, or a power source that is switched from the main power source as necessary. When a secondary battery is used as an auxiliary power source, the type of main power source is not limited to a secondary battery.

[0142] Specific examples of applications of secondary batteries are as follows: Electronic devices (including portable electronic devices) such as video cameras, digital still cameras, mobile phones, notebook computers, cordless phones, headphone stereos, portable radios, portable televisions, and portable information terminals; Portable household appliances such as electric shavers; Storage devices such as backup power sources and memory cards; Power tools such as electric drills and power saws; Battery packs mounted on notebook computers as removable power sources; Medical electronic devices such as pacemakers and hearing aids; Electric vehicles such as electric cars (including hybrid cars); Power storage systems such as home battery systems that store power in preparation for emergencies. The battery structure of the secondary battery may be the laminate film type and cylindrical type described above, or may be another battery structure. A plurality of secondary batteries may be used as a battery pack, a battery module, or the like.

[0143] In particular, battery packs and battery modules are effectively applied to relatively large devices such as electric vehicles, power storage systems, and power tools. As described below, the battery pack may use a single cell or a battery pack. An electric vehicle is a vehicle that operates (runs) using a secondary battery as a driving power source, and may be an automobile (such as a hybrid automobile) that also includes a driving source other than a secondary battery, as described above. A power storage system is a system that uses a secondary battery as a power storage source. In a home power storage system, power is stored in a secondary battery, which is a power storage source, and this power can be used to run home electrical appliances, etc.

[0144] Here, an example of an application of the secondary battery will be specifically described. The configuration of the application described below is merely an example and can be modified as appropriate.

[0145] Figure 3 shows the block configuration of a battery pack. The battery pack described here is a simplified battery pack (a so-called soft pack) that uses one secondary battery, and is installed in electronic devices such as smartphones.

[0146] 3, the battery pack includes a power source 41 and a circuit board 42. The circuit board 42 is connected to the power source 41, and includes a positive terminal 43, a negative terminal 44, and a temperature detection terminal 45. The temperature detection terminal 45 is a so-called T terminal.

[0147] The power source 41 includes one secondary battery. In this secondary battery, a positive electrode lead is connected to a positive electrode terminal 43, and a negative electrode lead is connected to a negative electrode terminal 44. This power source 41 can be connected to the outside via the positive electrode terminal 43 and the negative electrode terminal 44, and can be charged and discharged via the positive electrode terminal 43 and the negative electrode terminal 44. The circuit board 42 includes a control unit 46, a switch 47, a thermosensitive resistor element (Positive Temperature Coefficient (PTC) element) 48, and a temperature detection unit 49. However, the PTC element 48 may be omitted.

[0148] The control unit 46 includes a central processing unit (CPU) and a memory, and controls the operation of the entire battery pack. The control unit 46 detects and controls the usage state of the power source 41 as necessary.

[0149] When the battery voltage of the power source 41 (secondary battery) reaches the overcharge detection voltage or overdischarge detection voltage, the control unit 46 turns off the switch 47 to prevent the charging current from flowing through the current path of the power source 41. When a large current flows during charging or discharging, the control unit 46 turns off the switch 47 to cut off the charging current. The overcharge detection voltage and the overdischarge detection voltage are not particularly limited. As an example, the overcharge detection voltage is 4.2V±0.05V, and the overdischarge detection voltage is 2.4V±0.1V.

[0150] Switch 47 includes a charge control switch, a discharge control switch, a charge diode, and a discharge diode, and switches between the presence and absence of a connection between power source 41 and an external device in response to an instruction from control unit 46. Switch 47 includes a field effect transistor using a metal oxide semiconductor (Metal-Oxide-Semiconductor Field-Effect Transistor (MOSFET)), and the charge / discharge current is detected based on the ON resistance of switch 47.

[0151] Temperature detection unit 49 includes a temperature detection element such as a thermistor, measures the temperature of power supply 41 using temperature detection terminal 45, and outputs the temperature measurement result to control unit 46. The temperature measurement result measured by temperature detection unit 49 is used when control unit 46 performs charge / discharge control in the event of abnormal heat generation, and when control unit 46 performs correction processing when calculating remaining capacity. EXAMPLES

[0152] An embodiment of the present technology will be described.

[0153] (Experimental Examples 1-70) As described below, a laminate film type secondary battery (lithium ion secondary battery) shown in FIG. 1 and FIG. 2 was fabricated, and then the performance of the secondary battery was evaluated.

[0154] [Preparation of secondary battery] A secondary battery was fabricated by the following procedure.

[0155] (Preparation of positive electrode) First, a lithium compound (lithium sulfate), a nickel compound (nickel sulfate), a cobalt compound (cobalt sulfate), and a first other element compound (aluminum sulfate) were prepared as raw materials. Next, the lithium compound, the nickel compound, the cobalt compound, the first other element compound, and the second other element compound were mixed to obtain a precursor. In this case, the final product was a lithium nickel composite oxide (LiNi 0.80 Co 0.15 Al 0.05 Finally, the precursor was calcined to synthesize lithium nickel composite oxide (LiNi 0.80 Co 0.15 Al 0.05 O2) was synthesized. This resulted in the production of a positive electrode active material (lithium nickel composite oxide).

[0156] In this case, the firing temperature was changed within the range of 650°C to 800°C, thereby changing the intensity ratio IO as shown in Tables 1 to 5.

[0157] Next, 91 parts by mass of the above-mentioned positive electrode active material, 3 parts by mass of a positive electrode binder (polyvinylidene fluoride), and 6 parts by mass of a positive electrode conductive agent (graphite) were mixed to prepare a positive electrode mixture. Next, the positive electrode mixture was added to an organic solvent (N-methyl-2-pyrrolidone), and the organic solvent was stirred to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to both sides of a positive electrode current collector 11A (a strip-shaped aluminum foil having a thickness of 12 μm) using a coating device, and then the positive electrode mixture slurry was dried to form a positive electrode active material layer 11B. Next, the positive electrode active material layer 11B was compression molded using a roll press machine. Finally, the coating film 11C was formed in the stabilization treatment of the secondary battery described later, and thus the positive electrode 11 was produced, since the positive electrode active material layer 11B and the coating film 11C were formed on both sides of the positive electrode current collector 11A.

[0158] (Preparation of negative electrode) First, 93 parts by mass of the negative electrode active material (artificial graphite, which is a carbon material) and 7 parts by mass of the negative electrode binder (polyvinylidene fluoride) were mixed to prepare a negative electrode mixture. Next, the negative electrode mixture was added to an organic solvent (N-methyl-2-pyrrolidone), and the organic solvent was stirred to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of the negative electrode current collector 12A (strip-shaped copper foil with a thickness of 15 μm) using a coating device, and then the negative electrode mixture slurry was dried to form the negative electrode active material layer 12B. Finally, the negative electrode active material layer 12B was compression-molded using a roll press machine. As a result, the negative electrode active material layer 12B was formed on both sides of the negative electrode current collector 12A, and the negative electrode 12 was produced.

[0159] (Preparation of electrolyte) A boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound were added to a solvent (ethylene carbonate, which is a cyclic carbonate ester, and diethyl carbonate, which is a chain carbonate ester), and the solvent was stirred. The mixing ratio (weight ratio) of the solvents was ethylene carbonate:diethyl carbonate=50:50.

[0160] As the boron-containing compound, a boron-containing lithium salt that serves as an electrolyte salt was used. The type and content (wt%) of the boron-containing lithium salt are as shown in Tables 1 to 5. As the boron-containing lithium salt, lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiFOB), and lithium bis(oxalato)borate (LiBOB) were used. The above-mentioned "content (wt%)" is the content (wt%) when the solvent is 100 wt%, and the same applies hereinafter.

[0161] As the sulfur-containing compound, cyclic disulfonic anhydride and alkynyl sulfonate were used. The types and contents (wt%) of the cyclic disulfonic anhydride and alkynyl sulfonate are as shown in Tables 1 to 5. As the cyclic disulfonic anhydride, 1,3-propanedisulfonic anhydride (PSAH) and 1,2-ethanedisulfonic anhydride (ESAH) were used. As the alkynyl sulfonate, propargyl benzenesulfonate (PBS) was used.

[0162] As the fluorine-containing compound, a fluorine-containing lithium salt that serves as an electrolyte salt was used. The type and content (wt%) of the fluorine-containing lithium salt are as shown in Tables 1 to 5. As the fluorine-containing lithium salt, lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium tris(trifluoromethanesulfonyl)methide (LiFSC) were used.

[0163] As a result, the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound were each dispersed or dissolved in the solvent, and thus an electrolyte solution was prepared.

[0164] In this case, the respective contents of the boron-containing compound, the sulfur-containing compound, and the fluorine-containing compound were changed to change the respective intensity ratios IBN, ISN, and IFN as shown in Tables 1 to 5. Note that, during the synthesis of the above-described positive electrode active material, the intensity IN changed according to the change in the firing temperature, and therefore, the respective intensity ratios IBN, ISN, and IFN were also changed according to the change in the intensity IN.

[0165] For comparison, an electrolyte solution was prepared in the same manner except that no boron-containing compound, sulfur-containing compound, or fluorine-containing compound was used.

[0166] (Secondary battery assembly) First, an aluminum positive electrode lead 31 was welded to the positive electrode 11 (positive electrode current collector 11A), and a copper negative electrode lead 32 was welded to the negative electrode 12 (negative electrode current collector 12A).

[0167] Next, the positive electrode 11 and the negative electrode 12 were laminated with a separator 13 (a microporous polyethylene film having a thickness of 15 μm) interposed therebetween, and then the positive electrode 11, the negative electrode 12, and the separator 13 were wound to prepare a wound body. Next, the wound body was pressed using a press machine to mold the wound body into a flat shape.

[0168] Next, the roll was housed inside the recessed portion 20U provided in the exterior film 20. An aluminum laminate film in which a fusion layer (a polypropylene film having a thickness of 30 μm), a metal layer (aluminum foil having a thickness of 40 μm), and a surface protection layer (a nylon film having a thickness of 25 μm) were laminated in this order was used as the exterior film 20. Next, the exterior film 20 was folded so that the fusion layer was on the inside while sandwiching the roll, and then the outer peripheral edges of two sides of the exterior film 20 (fusion layer) were heat-sealed to each other to house the roll inside the bag-shaped exterior film 20.

[0169] Finally, after injecting the electrolyte into the bag-shaped exterior film 20, the outer peripheral edges of the remaining side of the exterior film 20 (bonding layer) were heat-sealed to each other in a reduced pressure environment. In this case, an adhesive film 21 (a polypropylene film having a thickness of 5 μm) was inserted between the exterior film 20 and the positive electrode lead 31, and an adhesive film 22 (a polypropylene film having a thickness of 5 μm) was inserted between the exterior film 20 and the negative electrode lead 32. As a result, the electrolyte was impregnated into the wound body, and the battery element 10 was produced. Thus, the battery element was enclosed inside the exterior film 20, and a secondary battery was assembled.

[0170] (Stabilization treatment) The secondary battery was charged and discharged for one cycle in a room temperature environment (temperature = 23°C). During charging, the battery was charged at a constant current of 0.1C until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05C. During discharging, the battery was discharged at a constant current of 0.1C until the voltage reached 3.0V. 0.1C is the current value at which the battery capacity (theoretical capacity) is fully discharged in 10 hours, and 0.05C is the current value at which the battery capacity is fully discharged in 20 hours.

[0171] As a result, coating 11C was formed on the surface of positive electrode active material layer 11B, and thus positive electrode active material layer 11B and coating 11C were formed on both sides of positive electrode current collector 11A, producing positive electrode 11. Thus, the state of the secondary battery was stabilized, and a laminate film type secondary battery was completed.

[0172] [Performance evaluation] When the performance (swelling characteristics) of the secondary battery was evaluated, the results shown in Tables 1 to 5 were obtained.

[0173] After the secondary battery was completed, the secondary battery was disassembled before examining the swelling characteristics, to recover the positive electrode 11, and then the surface of the positive electrode 11 was analyzed using XPS. Based on the surface analysis results of the positive electrode 11, the intensities of six types of XPS spectra (first O1s spectrum, second O1s spectrum, B1s spectrum, S2p spectrum, F1s spectrum, and Ni3p spectrum) were measured, and then four types of intensity ratios (intensity ratios IO, IBN, ISN, and IFN) were calculated based on the measurement results. The calculation results of the intensity ratios IO, IBN, ISN, and IFN are as shown in Tables 1 to 5.

[0174] When examining the swelling characteristics, first, the secondary battery was charged in a room temperature environment, and then the thickness of the secondary battery (thickness before storage) was measured. Next, the secondary battery in a charged state was stored (storage period = 24 hours) in a high temperature environment (temperature = 60 ° C.), and then the thickness of the secondary battery (thickness after storage) was measured again. Finally, the swelling rate (%) = (thickness after storage / thickness before storage) × 100 - 100 was calculated. The charging conditions were the same as those during the stabilization treatment of the secondary battery described above.

[0175] [Table 1]

[0176] [Table 2]

[0177] [Table 3]

[0178] [Table 4]

[0179] [Table 5]

[0180] [Consideration] As shown in Tables 1 to 5, the swelling ratio of the secondary battery in which the positive electrode 11 contains a lithium nickel composite oxide as the positive electrode active material varies greatly depending on the physical properties of the positive electrode 11 (intensity ratios IO, IBN, ISN, IFN).

[0181] Specifically, when a secondary battery in which the electrolyte did not contain a boron-containing compound, a sulfur-containing compound, or a fluorine-containing compound was subjected to stabilization treatment (Experimental Examples 66 to 70), all six types of XPS spectra were not detected, and therefore all four types of intensity ratios could not be calculated.

[0182] In contrast, when a secondary battery in which the electrolyte contained a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound was subjected to stabilization treatment (Experimental Examples 1 to 65), all six types of XPS spectra were detected, and all four types of intensity ratios could be calculated.

[0183] As a result, when the electrolyte did not contain a boron-containing compound, a sulfur-containing compound, or a fluorine-containing compound (Experimental Examples 66 to 70), the swollenness rate increased significantly.

[0184] In contrast, when the electrolyte contained a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound (Experimental Examples 1 to 65), the swelling ratio decreased. In this case, when the four conditions of intensity ratio IO=0.5 to 0.8, intensity ratio IBN=0.9 to 1.8, intensity ratio ISN=0.4 to 1.2, and intensity ratio IFN=8 to 13 were simultaneously satisfied (Experimental Examples 2 to 4, etc.), the swelling ratio further decreased compared to when the four conditions were not simultaneously satisfied (Experimental Examples 1 and 5, etc.), and therefore the swelling ratio decreased significantly.

[0185] (Experimental Examples 71 and 72) For comparison, as shown in Table 6, a secondary battery was fabricated in the same manner except that lithium cobalt oxide (LiCoO2) was used as the positive electrode active material instead of lithium nickel composite oxide, and the swelling characteristics of the secondary battery were evaluated.

[0186] [Table 6]

[0187] As shown in Table 6, in the secondary batteries (Experimental Examples 71 and 72) that did not use a lithium nickel composite oxide as the positive electrode active material, the swelling rate was reduced when the electrolyte contained a boron-containing compound, a sulfur-containing compound, and a fluorine-containing compound (Experimental Example 72) compared to when the electrolyte did not contain a boron-containing compound, a sulfur-containing compound, or a fluorine-containing compound (Experimental Example 71).

[0188] However, the swelling ratio in the case where the lithium nickel composite oxide was not used as the positive electrode active material (Experimental Example 72) was more than three times that in the case where the lithium nickel composite oxide was used as the positive electrode active material (Experimental Example 48). Therefore, the swelling ratio in the former case was not sufficiently reduced compared to the swelling ratio in the latter case.

[0189] The reason for this is believed to be due to the difference in the type of positive electrode active material. That is, the advantageous tendency that the swelling ratio is significantly reduced when the four conditions (intensity ratio IO = 0.5 to 0.8, intensity ratio IBN = 0.9 to 1.8, intensity ratio ISN = 0.4 to 1.2, and intensity ratio IFN = 8 to 13) are simultaneously satisfied is not obtained when a lithium nickel composite oxide is not used as the positive electrode active material, but is a unique tendency that is obtained only when a lithium nickel composite oxide is used as the positive electrode active material.

[0190] [summary] From the results shown in Tables 1 to 6, in a secondary battery in which the positive electrode 11 contains a lithium nickel composite oxide, when six types of XPS spectra (first O1s spectrum, second O1s spectrum, B1s spectrum, S2p spectrum, F1s spectrum, and Ni3p spectrum) were detected in the surface analysis of the positive electrode 11 using XPS, and the four types of intensity ratios (intensity ratios IO, IBN, ISN, and IFN) satisfied the above-mentioned conditions, the swollenness ratio was significantly reduced. Therefore, excellent swollenness characteristics were obtained in the secondary battery.

[0191] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the present technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.

[0192] Specifically, the battery structure of the secondary battery has been described as being of a laminate film type, but the battery structure is not particularly limited, and other battery structures such as a cylindrical type, a square type, a coin type, and a button type may also be used.

[0193] In addition, although the battery element has a wound structure, the element structure of the battery element is not particularly limited, and may be other element structures such as a stacked type in which the electrodes (positive and negative electrodes) are stacked, or a zigzag-folded type in which the electrodes (positive and negative electrodes) are folded.

[0194] Furthermore, although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.

[0195] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.

Claims

1. a positive electrode including a lithium nickel composite oxide; A negative electrode; Electrolyte and Equipped with In a surface analysis of the positive electrode using X-ray photoelectron spectroscopy, A first O1s spectrum having a peak in a binding energy range of 528 eV or more and 531 eV or less; a second O1s spectrum having a peak in a range of binding energies greater than 531 eV and less than or equal to 535 eV; B1s spectrum; S2p spectrum; F1s spectrum; Ni3p spectrum and is detected, a ratio of an intensity of the first O1s spectrum to an intensity of the second O1s spectrum is equal to or greater than 0.5 and equal to or less than 0.8; a ratio of the intensity of the B1s spectrum to the intensity of the Ni3p spectrum is 0.9 or more and 1.8 or less; a ratio of an intensity of the S2p spectrum to an intensity of the Ni3p spectrum is 0.4 or more and 1.2 or less; The ratio of the intensity of the F1s spectrum to the intensity of the Ni3p spectrum is 8 or more and 13 or less. Secondary battery.

2. The positive electrode is a positive electrode active material layer containing the lithium nickel composite oxide; a coating film provided on the surface of the positive electrode active material layer and containing boron, sulfur and fluorine as constituent elements; Including, The coating is analyzed by surface analysis of the positive electrode using X-ray photoelectron spectroscopy. The secondary battery according to claim 1 .

3. The lithium nickel composite oxide contains a compound represented by the following formula (1): The secondary battery according to claim 1 or 2. Li w Ni (1-x-y-z) Co x M1 y M2 z O 2 ・・・(1) (M1 is at least one of Al and Mn. M2 is at least one of elements belonging to groups 2 to 15 of the long-form periodic table (excluding Ni, Co, Al, and Mn). w, x, y, and z satisfy 0.8≦w≦1.2, 0≦x≦0.3, 0≦y≦0.1, and 0≦z≦0.

1. However, the composition of lithium varies depending on the charge / discharge state, and w is the value in a fully discharged state.)

4. The electrolyte solution is A boron-containing compound; A sulfur-containing compound; Fluorine-containing compounds The secondary battery according to claim 1 , further comprising:

5. the boron-containing compound comprises a boron-containing lithium salt; The sulfur-containing compound includes at least one of a cyclic disulfonic anhydride and an alkynyl sulfonate; The fluorine-containing compound includes a fluorine-containing lithium salt. The secondary battery according to claim 4.

6. Further, a flexible exterior member is provided to accommodate the positive electrode, the negative electrode, and the electrolyte. The secondary battery according to claim 1 .

7. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Rational beekeeping method and apparatus in large composite unit for honeybee

    JP1981045144A

  • Battery

    JP2008098053A

  • Nonaqueous electrolyte secondary battery

    JP2009224097A

  • Electrolyte, and secondary battery

    JP2010225522A

  • Positive electrode active material, nonaqueous electrolyte battery and manufacturing method of positive electrode active material

    JP2012018827A